Effects of different characteristic surfaces at initial stage of frost growth - Cai, Liang; Hou, Pu-xiu; Wang, Rong-han; Zhang, Xiao-song (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2010)
The effects of surface energy on phase change of water vapor at initial stage of frost growth were studied to find an effective method of restraining frost growth. The mechanism of restraining frost growth by low energy surface (bigger contact angle) was analyzed based on crystal growth theory. Then, the phase change of water vapor and the process of frost growth on the copper and wax energy surfaces were observed using microscope. The results indicate that it is difficult for wax surface (low energy surface), on which there are still water droplets at 100 s, to form critical embryo, so frost growth can be restrained in a way. Water formation, droplet growth, ice formation and dendritic ice growth processes happen on both surfaces, ordinally. But the ice beads, with larger average diameter and sparse distribution on the wax surface, form later (at about 300 s) than that on the copper surface, and the dendritic ice also appears later. All of these support that ice crystal formation and dendritic crystal growth at initial stage of frost growth can be retarded on the low energy surface.